Ethical Dimension of Time in Plato’s Apology of Socrates - Pacewicz, Artur (Peitho. Examina Antiqua, 2011)
The aim of the present article is to analyse the Apology in its aspect of time. When defending himself against the charges, Socrates appeals to the past, the present and the future. Furthermore, the philosopher stresses the meaning of the duration of time. Thus, the seems to suggest that all really important activities demand a long time to benefit, since they are almost invariably connected with greater efforts. While the dialogue proves thereby to be an ethical one, the various time expressions also gain an ethical dimension.